Influence of surface properties on soccer ball trajectories - Goff, J. E.; Hong, S.; Asai, T. (Proceedings, 2020)
In this paper, we summarize our recent research work on soccer balls. Employing wind tunnels and analyses of simulated trajectories, we have gained an understanding of how various surface features influence soccer ball aerodynamics. Wind tunnels provide aerodynamic coefficients for non-spinning soccer balls. The coefficients then help determine the trajectories of various simulated kicked balls. Surface features include panel texturing, seam width, and seam depth. We have determined that small changes in surface texturing can lead to hard-kicked soccer balls experiencing lateral deflections as large as 10%-20% of their horizontal ranges. We have also found that the critical Reynolds number for soccer balls is more strongly correlated with seam width than with seam depth.